2010
DOI: 10.1111/j.1468-1331.2009.02884.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of sleep in primary focal dystonia: a case–control study

Abstract: Background: Sleep disturbances are common in patients with movement disorders. Evaluating quality of sleep is of primary importance because of the effect that nocturnal and daytime sleep abnormalities exert on general health status. However, quality of sleep has never been addressed in detail in patients with dystonia. The aim of this case-control study was to analyse quality of sleep in patients with the two most common forms of primary focal dystonia, blepharospasm (BSP) and cervical dystonia (CD). Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
50
0
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 30 publications
8
50
0
13
Order By: Relevance
“…Lack of correlation between PSQI and severity of dystonia in both CD and BSP patients suggested that insomnia might be a comorbidity disorder in patients with BSP or CD, which partly resemble the results of Avanzino et al. (2010). After ANCOVA analysis to avoid the influence of anxiety and depression, insomnia showed tight connection with depression, but the causal relationship between quality of sleep and depression remains unknown (Lobbezoo, Thu Thon, Remillard, Montplaisir, & Lavigne, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lack of correlation between PSQI and severity of dystonia in both CD and BSP patients suggested that insomnia might be a comorbidity disorder in patients with BSP or CD, which partly resemble the results of Avanzino et al. (2010). After ANCOVA analysis to avoid the influence of anxiety and depression, insomnia showed tight connection with depression, but the causal relationship between quality of sleep and depression remains unknown (Lobbezoo, Thu Thon, Remillard, Montplaisir, & Lavigne, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Besides PSQI, we used ESS to evaluate daytime sleepiness. It's interesting to find that the impairment of sleep quality did not have impact on daytime sleepiness, which was similar with another study (Avanzino et al., 2010). Overall, insomnia is a feature of primary cranial and cervical dystonia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cause of CD remains unknown but in addition to motor symptoms CD is associated with nonmotor symptoms such as sensory deficits, sleep disorders, and pain (Avanzino et al., 2010; Antelmi et al., 2016; Tinazzi, Fiorio, Fiaschi, Rothwell, & Bhatia, 2009; Patel, Jankovic, & Hallett, 2014). Impaired sensorimotor integration has been described as part of the pathophysiology of CD (Tinazzi, Rosso, & Fiaschi, 2003; Fiorio et al., 2007; Konczak & Abbruzzese, 2013).…”
Section: Introductionmentioning
confidence: 99%